由方程[img=182x39]180355664b2677f.png[/img]确定的隐函数[img=66x25]180355665324074.png[/img]的导数[img=78x44]180355665bdd53b.png[/img]
未知类型:{'options': ['', '', '', ''], 'type': 102}
未知类型:{'options': ['', '', '', ''], 'type': 102}
举一反三
- 由方程[img=182x39]180355664b2677f.png[/img]确定的隐函数[img=66x25]180355665324074.png[/img]的导数[img=78x44]180355665bdd53b.png[/img] A: [img=42x45]1803556663af424.png[/img] B: [img=58x45]180355666ba229c.png[/img] C: [img=42x45]1803556673ac85c.png[/img] D: [img=58x45]180355667c6de2b.png[/img]
- 由方程[img=182x39]18035555ab8dba0.png[/img]确定的隐函数[img=66x25]18035555b4857d1.png[/img]的导数[img=78x44]18035555bda7e3b.png[/img] 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 由方程[img=113x26]180350a9b878a46.png[/img]所确定的隐函数y对x的导数[img=20x44]180350a9c154c58.png[/img]是( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 2、由方程[img=182x28]1802e444a9d8219.png[/img]确定函数y=f(x)的二阶导数[img=27x46]1802e444b2473e0.png[/img]为( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 2、由方程[img=182x28]1802e44234cea13.png[/img]确定函数y=f(x)的二阶导数[img=27x46]1802e4423cf0f43.png[/img]为( ) 未知类型:{'options': ['', '', '', ''], 'type': 102}